Uma Análise de Construtos Teóricos Sobre Participação e Gestão Social - Júlio Cesar Andrade de Abreu (Desenvolvimento em Questão, 2019)
The genesis of the concept of social management is a product of the need to establish new benchmarks for public administration, guided by the collective definition of goals and means and by the intersection of values, knowledge and worldviews. Starting from this fact, the article tries to respond the following question: how do some theoretical constructs about participation contemplate the principles of inclusion, pluralism, equality, autonomy and common good, sources of legitimacy of public deliberation and premises of deliberative citizenship? Using the bibliographical research were analyzed the constructs on participation of Nogueira (2005), Arnstein (1969), Bordenave (1983) and Pretty (1995). This work intends to contribute to the strengthening of the conceptual debate on social management, correlating it with different theoretical elaborations associated with participation.